Using English-Subtitled YouTube Narrative Videos to Improve EFL Listening Comprehension in a Vocational High School - Maharani Rizka Ramadhani Wijaya; Wanamileen Waehayee (New Language Dimensions, 2026)
This study investigated the effect of English subtitles in YouTube narrative videos on the listening comprehension of eleventh-grade vocational high school students in Indonesia. A quantitative quasi-experimental design was employed using pre-test and post-test measures with a control group. Two intact classes participated in the study: 25 students in the experimental group and 25 students in the control group. The experimental group learned through YouTube narrative videos with English subtitles, while the control group watched the same videos without subtitles. Data were collected using a 25-item listening comprehension test and analyzed using descriptive statistics, paired sample t-tests, an independent sample t-test, and effect size analysis. The findings showed a significant difference in post-test scores between the experimental and control groups, with the experimental group achieving higher listening performance (p = 0.010 < 0.05). The experimental group also showed significant improvement after the treatment (p = 0.008 < 0.05), whereas the control group did not show a significant gain. These results suggest that English subtitles can serve as effective instructional scaffolding for improving students’ listening comprehension, particularly in vocational EFL classrooms where learners may have limited exposure to authentic spoken English.